PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) BERBASIS MEDIA TERHADAP KEMAMPUAN BERPIKIR SISWA KELAS VIII PADA MATA PELAJARAN MATEMATIKA DI UPT SPF SMPN 21 MAKASSAR - Nafisah; Nurdin; Wahyuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine what is the effect of the media-based Problem Based Learning (PBL) model on students' thinking skills and how the Problem Based Learning (PBL) model affects the thinking skills of class VIII students in Mathematics subjects at UPT SPF SMPN 21 Makassar. This type of research is quantitative research with experimental method (pre experiment) one group Pretest-Posttest design. The population in this study were all students of class VIII UPT SPF SMPN 21 Makassar consisting of 7 classes with a total of 208 people. The samples in this study were students of class VIII.A, VIII.B, VIII.C, with a total of 68 people selected through Cluster random sampling with the determination of the number of samples using the Slovin formula. Data collection techniques in this study were observation, questionnaire, test, and documentation. The results of this study indicate that the effect of using a media-based problem-based learning model on students' thinking skills has been achieved. This can be seen from the calculation of the tcount value = 18.723 and the ttable value = 1.668, based on the test criteria if tcount> ttable then H0 is rejected and H1 is accepted. This proves that there is an effect of using a media-based problem-based learning model on students' thinking skills. In addition, the results of this study also show that the use of media-based problem-based learning models on thinking skills has been achieved or effective and affects students' thinking skills through an approach that combines problem solving with active learning.